APPLICATION OF TAGUCHI TECHNIQUES TO STUDY DRY SLIDING WEAR BEHAVIOUR OF MAGNESIUM MATRIX COMPOSITES REINFORCED WITH ALUMINA NANO PARTICLES - TARASASANKA C.; RAVINDRA K. (Journal of Engineering Science and Technology, 2017)
Magnesium metal matrix composites reinforced with alumina Nano particles are prepared by liquid metallurgy route. Dry sliding wear behavior of the composite was tested and compared with AZ91 magnesium alloy. A design of experiments based on Taguchi technique is used to acquire the data in a controlled way. An L9 orthogonal array is employed to trace out the influence of wear parameters like Sliding Speed, Applied Load, Sliding Distance and Percentage of reinforcement on dry sliding wear of the composites. Objective of the model was chosen as “smaller the better” characteristics to analyse the dry sliding wear behaviour. Results show that sliding distance has the highest influence on wear and load is predominant factor on the response of friction. The mathematical model was developed using regression analysis to determine the wear and friction force of composites.